Transient scrotal hyperthermia affects human sperm DNA integrity, sperm apoptosis, and sperm protein expression. (13th July 2016) - Rao, M.; Xia, W.; Yang, J.; Hu, L.‐X.; Hu, S.‐F.; Lei, H.; Wu, Y.‐Q.; Zhu, C.‐H.
Summary: This prospective randomized clinical study is aimed to evidence the reproductive impairment of frequent scrotal heat exposure. A total of 20 normozoospermic subjects were randomly divided into two groups to undergo testicular warming in a 43 °C water bath 10 times, for 30 min each time; the subjects in group 1 underwent testicular warming for 10 consecutive days and those in group 2 once every 3 days. Sperm chromatin structure assay (SCSA), sperm mitochondrial membrane potential (MMP), apoptosis, and seminal plasma‐soluble Fas (sFas) were analyzed before treatment and every 2 weeks after, for a total of 10 times. In group 1, some critical proteins involved in heat stress, hypoxia, structure, and function of sperm mitochondria and flagella were evaluated before hyperthermia and 2, 6, 10, and 16 weeks after hyperthermia. Both groups showed a reversible increase in the proportion of spermatozoa with a disrupted MMP (both p < 0.05 when the minimums were compared with baseline levels, the same below), sperm apoptosis (both p < 0.01) and high DNA stainability (both p < 0.05). The sFas concentration in both groups showed no obvious changes except one: the value at week 2 was significantly increased over baseline in group 1 ( p = 0.036). The level of Bcl‐2 decreased significantly at weeks 6 and 10 ( p = 0.017 and 0.05, respectively) and recovered to baseline at week 16. Proteins involved in heat stress and mitochondria functions were up‐regulated, whereas in flagella structure and function was down‐regulated (all p < 0.05). This study demonstrated that transient and frequent scrotal hyperthermia severely and reversibly damaged spermatogenesis, consecutive heat exposure had more serious effects than intermittent exposure, whereas intermittent exposure led to a later recovery of sperm damage.